PEMBERDAYAAN KELUARGA, DUKUNGAN SOSIAL, DAN EFIKASI DIRI DALAM MENINGKATKAN KEPATUHAN PENGOBATAN TUBERKULOSIS: TINJAUAN LITERATUR - Haryanto, Mokhamad Sandi (JURNAL KEPERAWATAN, 2026)
Background: Tuberculosis (TB) treatment requires long-term adherence, often complicated by social, psychological, and family-related factors. Family support, empowerment, and patient self-efficacy have been suggested to improve treatment adherence and outcomes. Objective: To synthesize evidence on the effectiveness of family support, self-efficacy, and related interventions in improving TB treatment adherence using the PICOT framework. Methods: A narrative literature review of 10 studies (2017–2025) was conducted. Studies were selected based on relevance to family support, self-efficacy, and TB treatment adherence. Evidence was summarized according to the PICOT elements. Results: Family support and self-efficacy significantly improved patient adherence, self-care, and psychosocial well-being. Interventions included counseling, family education, and social support. Most studies were cross-sectional, limiting causal inference, and relied on self-report. Outcome measures varied, with limited long-term follow-up and few clinical outcome assessments. Conclusion: Family-centered and self-efficacy–enhancing interventions are effective strategies to improve TB treatment adherence. Future research should adopt longitudinal or experimental designs to evaluate clinical outcomes and intervention sustainability